Church and Pacifism: The Role of Religion in the Face of Security Threats (Politeja, 2019)
The article is a study in the domain of security and aims to answer the following question in the context of contemporary threats: What is the Catholic Church’s attitude towards pacifism? The author presents research concerning the relationship between pacifism and religion, analyzing the question of pacifism with reference to biblical texts and contemporary Catholic thought.